Right to left interatrial communications after the modified Fontan procedure: identification and management with transcatheter occlusion. - Hsu, H. S. (1995)
OBJECTIVE--To describe unusual venous communications from the right to the left atrium resulting in cyanosis after the modified Fontan procedure, and their management with transcatheter occlusion. METHODS--Between September 1992 and November 1994, eight patients were assessed for persistent cyanosis after a modified Fontan procedure. Desaturation was found to be caused by unusual venous shunts originating at atrial level, and transcatheter occlusion with either a double umbrella or coil was attempted. RESULTS--Three types of venous channels were identified. The first type of communication consisted of thin long tortuous channels originating from the right atrial wall, and draining into the left atrium through a capillary network. The second type of communication was in the superior anterior portion of the atrial baffle, incorporating the pectinate muscles of the right atrium, draining into the neoleft atrium. These channels were shorter and often fanned out into small vessels toward the right atrial appendage. In each instance, the shunts were in the superior suture line of a lateral tunnel modification of the Fontan procedure. The third type of communication originated from the inferior vena cava, connecting inferior phrenic veins to pericardial veins and subsequently to the left atrium, at or close to the ostium of the left pulmonary veins. Before device occlusion, the room air aortic oxygen saturation was 88(SD 4)% (range 84% to 94%), and increased to 95(3)% (range 91% to 100%) following occlusion (PL << 0.001). The mean right atrial pressure was 14(4)mm Hg and remained unchanged after occlusion. In six patients there was complete shunt obliteration, while in two both occluded with umbrella devices, a small residual leak persisted. No complication occurred during or immediately after catheterisation. CONCLUSIONS--Unusual venous communications can evolve after the Fontan procedure, resulting in the development or persistence of cyanosis. Some of these communications may be present preoperatively as normal veins draining into the right atrium, enlarging with the increased atrial pressure after surgery. These observations affect long term function after the Fontan procedure. Transcatheter occlusion of these communications is technically feasible and effective, although recurrence may occur.